2010
DOI: 10.1002/stem.316
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Influences the Vascular Expansion and Differentiation of Embryonic Stem Cell Cultures Through the Temporal Expression of Vascular Endothelial Growth Factor Receptors in an ARNT-Dependent Manner

Abstract: Adaptive responses to low oxygen (O 2 ) tension (hypoxia) are mediated by the heterodimeric transcription factor hypoxia inducible factor (HIF). When stabilized by hypoxia, bHLH-PAS a-and b-(HIF-1b or ARNT) HIF complex regulate the expression of multiple genes, including vascular endothelial growth factor (VEGF). To investigate the mechanism(s) through which hypoxia contributes to blood vessel development, we used embryonic stem cell (ESC) differentiation cultures that develop into embryoid bodies (EBs) mimick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 48 publications
2
36
0
Order By: Relevance
“…To generate gelatin-adapted ESCs, cells were weaned off feeder cells by serial passages on 6-well plates coated with 1% gelatin (Sigma) as described elsewhere (31)(32)(33)(34).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To generate gelatin-adapted ESCs, cells were weaned off feeder cells by serial passages on 6-well plates coated with 1% gelatin (Sigma) as described elsewhere (31)(32)(33)(34).…”
Section: Methodsmentioning
confidence: 99%
“…For hematopoietic differentiation, a two-step differentiation method was used as described (31). For primary differentiation, gelatin-adapted ESC (3,000 cells) were seeded on methylcellulose-based semi-solid media containing Iscove's modified Dulbecco's medium, 15% FBS (STEMCELL Technologies), IL-3, and stem cell factor (R&D Systems) as described previously (31).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ESCs were induced to differentiate via a methylcellulose-based method as described previously (22). For hypoxia experiments, ESCs were cultured or induced to differentiate in an incubator with an adjustable oxygen concentration, as described elsewhere (24).…”
Section: ⌬/ϫmentioning
confidence: 99%
“…Physiological oxygen levels that occur during early embryo development have been shown to maintain ESC in a pluripotent state [29][30][31] and to improve their directed differentiation towards cardiac [15,20], vascular [32], neural [33][34][35][36][37] and retinal lineages [38]. Studies from our laboratory revealed that the yield of neural cells from mouse ESC (mESC) can be greatly enhanced by manually operating at 2% O 2 [33].…”
Section: Introductionmentioning
confidence: 99%